PERILAKU PACARAN DAN MORAL SISWA DI SMP NEGERI 40 PEKANBARU - Gusriana Rahmayani; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The phenomenon of behavioral changes and moral damage that occurs in adolescents today has come to a very poor condition, where many teenagers who experience moral degradation in various aspects ranging from speech, how to dress up dating behavior. The purpose of this study is to determine the behavior of students who are flirting and know the moral behavior of students who are flirting. sample of this research there are students who dating as many as 48 people by using purposive sampling. This research uses descriptive method with quantitative approach. In this study the instrument used is a closed questionnaire. To analyze data use using the percentage formula. The conclusion from the result of this research indicates that student dating behavior in SMP Negeri 40 Pekanbaru is still in normal category, showing only sympathy and empathy toward the opposite sex, While the moral of students who are dating is included in the category of less good because the students are dating always to the parents.Key Words : Behavior, Flirtation, Moral